Multifunctional hybrid polymer nanocomposites for automotive‐battery packaging. Issue 36 (14th February 2020) - Yoo, Joung Eun; Roev, Victor; Bae, Joonho; Yoon, Du‐Seop; Kim, Sung‐Dug; Lee, Eun‐Sung
Abstract: Global sales of new electric vehicles (EV) already passed a million units last year. Lithium‐ion battery packs are composed of cells and assembly of modules. Nevertheless, the development of light‐weighted with high oxygen and moisture barrierability remains one of the untouched issues in battery technology. This study aimed to fabricate multifunctional hybrid nanocomposites for barrier films for Li‐ion battery packs on electric vehicles applications. The synthesized carbon supported MgO nanoparticles (hereafter referred to as CSMO) were dispersed in high density polyethylene (HDPE) polymer to satisfy several requirements for EV battery packs. The loading amount of MgO was achieved up to 22 wt % of carbon, and the size distribution was in the range of 50 to 100 nm. The hybrid nanocomposites were characterized by water‐vapor transmission rate (WVTR), various spectroscopic methods, thermo‐gravimetric analysis and elemental analysis. Mechanical properties were also tested. The extremely low WVTR value of CSMO/HDPE composites below 0.5 mgm −2 day −1 is the lowest value among any other gas barrier films reported in the literature. Suitable mechanical properties were also achieved. The newly proposed multifunctional hybrid nanocomposites would be very promising for barrier films on automotive packaging applications. Abstract :